Normal academic stream students' difficulties in solving algebraic word problems in secondary school - Ng, Siew Lai. (2008)
The purpose of this study is to find out the difficulties faced by Secondary School students from the Normal Academic stream in solving algebraic word problems and what are the causes of such difficulties.